2019
DOI: 10.1002/jcla.22917
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating lnc‐ANRIL/miR‐125a axis level predicts higher risk, more severe disease condition, and worse prognosis of sepsis

Abstract: Aim This study aimed to investigate the correlation of lnc‐ANRIL/miR‐125a axis with risk, severity, inflammation, and prognosis of sepsis. Methods A hundred and twenty‐six sepsis patients and 125 healthy controls were recruited, and then, blood samples were collected, and plasma was separated for lnc‐ANRIL, miR‐125a, lnc‐ANRIL/miR‐125a axis, and inflammatory cytokine level detections. In addition, basic characteristics, 28‐day mortality, and accumulating survival of sepsis patients were recorded. Results Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…The possible reasons may include that according to the previous studies miR-125a may inhibit the phagocytic and bactericidal activities through suppressing macrophage M1 functionality, and psoriatic patients had increased levels of inflammatory cytokines compared with HC; therefore, miR-125a expression was decreased in psoriatic patients. 22 According to the previous studies, miR-125a plays an important role in regulating TNF-a level as well as inflammatory responses; meanwhile, it has potential for predicting treatment response to TNF inhibitor as well as survival profiles in patients with inflammatory-related diseases. Further, considering the previous studies, miR-125a reduced the production of inflammatory mediators and decreased the subsequent secretion of inflammatory cytokines, and miR-125a served an inhibitory role in cell proliferation, miR-125a may alleviate inflammatory effects on skin lesions and decrease epidermal hyperplasia; therefore, miR-125a was negatively associated with disease severity in psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible reasons may include that according to the previous studies miR-125a may inhibit the phagocytic and bactericidal activities through suppressing macrophage M1 functionality, and psoriatic patients had increased levels of inflammatory cytokines compared with HC; therefore, miR-125a expression was decreased in psoriatic patients. 22 According to the previous studies, miR-125a plays an important role in regulating TNF-a level as well as inflammatory responses; meanwhile, it has potential for predicting treatment response to TNF inhibitor as well as survival profiles in patients with inflammatory-related diseases. Further, considering the previous studies, miR-125a reduced the production of inflammatory mediators and decreased the subsequent secretion of inflammatory cytokines, and miR-125a served an inhibitory role in cell proliferation, miR-125a may alleviate inflammatory effects on skin lesions and decrease epidermal hyperplasia; therefore, miR-125a was negatively associated with disease severity in psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-125a is also reported to serve as a potential prognostic biomarker in autoimmune and inflammatory diseases. 14,22 For example, miR-125a level is reported to be of value in predicting clinical remission after TNF inhibitor and/or immunosuppressive agent treatment in active Crohn's disease patients. 14 In another study, sepsis patients with low miR-125a expression presented with worse accumulating survival compared with those with high miR-125a expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative expressions of lncRNA NEAT1 and miR‐125a in plasma of patients and HCs were determined by reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR). The RT‐qPCR was performed according to the method described in our previous study, 17 and the primers were as follows: LncRNA NEAT1, Forward (5′‐>3′): TGTCCCTCGGCTATGTCAGA; Reverse (5′‐>3′): GAGGGGACGTGTTTCCTGAG. MiR‐125a, Forward (5′‐>3′): ACACTCCAGCTGGGTCCCTGAGACCCTTTAAC; Reverse (5′‐>3′): TGTCGTGGAGTCGGCAATTC.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies demonstrated that the lnc-ANRIL/miR-125a axis could serve as a predictor for prognosis, severity, and inflammation among sepsis patients (91)(92)(93). LncRNA ANRIL is the prime candidate gene at Chr9p21 and widely recognized as a critical part of endothelial inflammation and cell proliferation (91,(94)(95)(96)(97).…”
Section: Anrilmentioning
confidence: 99%